Tori Brunger: capstone - Brunger, Tori, artist (Colorado State University. Libraries, 2026)
The artist's statement: My name is Tori Brunger, and I am a Graphic Designer and Electronic artist. As I was doing research on what designs and ideas I wanted to implement, I was really drawn to the designs that involved birds. I often think of birds as one of the freest living creatures with their ability to defy gravity and began thinking about how I could incorporate birds and what they symbolize into a design about human rights. Then Jason told a story about the time he saw a falcon chased out of a tree by a group of smaller birds. That really resonated with me how the power of numbers, even if the birds are small, can fight and chase off a bigger threat and how that can apply to the fight for human rights. Using doves as a symbol for peace and unity and crows as a symbol for death and oppression, I designed a tree being claimed by a group of doves as they chase off a flock of invading crows. This design is meant to show that no matter how small, when we fight for human rights, we can chase off even the biggest oppressors. I also used the colors and effect of a sunrise to symbolize the dawn of a new day on the fight for human rights.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design